A randomised wait-list controlled clinical trial of the effects of acceptance and commitment therapy in patients with type 1 diabetes: a study protocol. Issue 1 (December 2015) - Lindholm-Olinder, Anna; Fischier, Johan; Fries, Jenny; Alfonsson, Sven; Elvingson, Veronika; Eriksson, Jan; Leksell, Janeth
Abstract Background In order to manage the acute and long-term effects of living with a chronic disease such as diabetes, both medical treatment and good psychosocial support are needed. In this study, we wish to examine whether a psychological group intervention targeting people with poorly controlled type 1 diabetes can be helpful in augmenting quality of life while also lowering participants' HbA1c level. The group intervention will consist of a brief treatment developed from a branch of cognitive behavioural therapy called acceptance and commitment therapy, which is part of the so-called third wave of cognitive behavioural therapy. Common for these third-wave therapies, the focus is less on the content and restructuring of thoughts and more on the function of behaviour. Here, we describe the protocol and plans for study enrolment. Methods/Design This on-going study is designed as a randomised wait-list controlled trial. Eighty patients aged 26–55 years and with an HbA1c level >70 mmol/mol at the time of enrolment will be included. Discussion In this study, we will assess the effect of starting acceptance and commitment therapy group treatment for patients with type 1 diabetes and its effect on glycaemic control and well-being. Trial registration Current controlled trials:ISRCTN17006837, registered 12th January 2015